Maternal is Factors Associated with Low Birth Weight Babies - Muhammad Ashraf; Umar Hayat Khan, Ahmad Ali, Ariz Madan Khattak , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2014)
Objective: The present study was conducted to know the maternal risk factors of LBW babies. Place & Duration: This cross-sectional analytical study was carried out in the teaching hospital of Khyber Medical University Institute of Medical Sciences, Kohat, from 1 stSeptember, 2012 to 10th October, 2013. Material and Methods: 100 apparently healthy mothers of full term pregnancy with normal vaginal singleton viable babies with low birth weight were included in the study and they were interviewed using structured questionnaire. All the mothers with preterm infants, twins, or those born via Cesarean section were not included in our study. Newborns weighing < 2500 gram were labelled as low birth. The mothers were analyzed for the risk factors of LBW including mother's age, height, Body Mass Index (BM), level of antenatal care, level of education, socioeconomic status and the area of residence. Results: Out of 100 mothers aged between 18 to 35 years, 64 belong to rural areas while 36 belong to urban locality. 27 percent were completely uneducated while 73 percent were educated to different levels. 55 out of 100 respondents were underweight (BMI < 18 kg/m2) with 23 Grand Multi Para. Majority of them 53')/o belong to poor families and 41 / -0 had 3 or more ante-natal visits. Conclusion: Low maternal level of education, low BMI„ poverty and less antenatal visits are important risk factors for LBW.